THRUST & SMART Home for Elderly Talk by Prof. Halimahtun & Prof. Martin - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innova (Universiti Malaysia Sarawak (UNIMAS), 2014)
"Trusting Humanoid Robot Undertake Social Tasks" by Professor Halimahtun M. Khalid from Damai Sciences, Malaysia and "Analyzing the Needs for Smart Homes for the Elderly" by Professor Martin G. Helander from Nanyang Technological University,Singapore